Carvão ativado obtido a partir da palha de azevém (Lolium multiflorum Lam.) para a adsorção do corante azul de metileno - Silva, Elenara Oliveira da (2019)
The ryegrass (Lolium multiflorum Lam.) is a winter forage largely cultivated in the southern Brazil and its responsible for a large quantity of residues (straw) after the harvests. This residue may be a potential adsorbent as well as a precursor to the production of activated carbon for wastewater treatment. In this view, the present study focuses on the use of ryegrass straw in natura treated and modified for activated carbon, as adsorbents of methylene blue dye. The straw was chemically treated with NaOH and H3PO4 and activated carbons were produced by chemical activation. The adsorbents were characterized by physical and physicochemical characterization, with particle diameter, bed porosity, real and bulk density, TGA, XRD and proximate analysis. For the activated carbons, the specific surface area and average pore diameter were also analyzed. Kinetic experiments and adsorption isotherms were performed, and the data were fitted using models predicted in the literature. The results for TGA and XRD characterization show that both NaOH and H3PO4 caused degradation of hemicellulose and cellulose of the ryegrass straw. It led to changes in the material structure, possibly increasing the surface area of the adsorbents. NaOHactivated carbon had a surface area of 29.63 m2 /g and H3PO4-activated carbon 68.28 m2 /g. Ryegrass straw in natura had a maximum adsorption capacity of 28.7 mg/g. The ryegrass straws treated with NaOH and H3PO4 showed qmax values up to 70.9 mg/g and 80.79 mg/g. For activated carbons, the values of qmax were 25.73 mg/g and 53.32 mg/g. These results demonstrated that the treated ryegrass straws have a great potential for methylene blue dye removal, reaching efficiencies up to 99% in the concentrations used.